Polycyclic Aromatic Hydrocarbons from Fine Particulate Matter Induce Oxidative Stress and the Inflammatory Response in Human Vocal Fold Fibroblast Cells. (4th August 2021) - Choi, Hyunsu; Kim, Choung-Soo
Abstract : Polycyclic aromatic hydrocarbons (PAHs) are toxicants in particulate matter (PM). The vocal fold, part of the larynx and a key structure for voicing, is always in contact with air. In recent epidemic studies, PM was shown to cause laryngitis; however, the basic mechanism has not been evaluated. In the present study, intracellular reactive oxygen species (ROS) and proinflammatory cytokine levels were analyzed after exposing human vocal fold fibroblasts (hVFFs) to PM standard reference material (SRM 2786). Expression levels of the aryl hydrocarbon receptor (AhR) and Cytochrome P450 Family 1 Subfamily A Member 1 (CYP1A1) were also evaluated. PM induced ROS formation and proinflammatory cytokines via the AhR CYP1A1 pathway and caused lipid peroxidation and DNA damage. Blocking AhR or CYP1A1 production using siRNAs significantly decreased ROS production and IL-6 and IL-9 expression in PM-exposed hVFFs, thus protecting the cells against oxidative stress. These results confirm that PAHs in PM play an important role in cell damage and inflammation, confirming a basic pathophysiologic relationship between PM exposure and laryngitis.